Role of surface to volume ratio of zinc oxide arrester on energy absorption capability - Karim, A.N. Mustafizul; Begum, Shahida (2013)
Functional life of a zinc oxide arrester block is largely dependent on its energy absorption capability which is an important characteristic in ensuring enhanced reliability of a surge protection system. An arrester block is usually cylindrical in shape with two flat surfaces. Injected energy from the stroke of transient electrical surge into the arrester body is transformed into heat and dissipated through the surface of the disc body. This study has been conducted to observe whether the higher surface to volume (S/V) ratio of an arrester block enhances the capability of energy absorption or not. The round side or C-surface of the cylindrical disc was ground by diamond wheel to transform into hexagonal shape. By making this geometrical modification an increase of about 11% in S/V ratio was achieved for the hexagonal discs. Ten ZnO arrester blocks of both shapes were tested and the average energy absorption capability for the hexagonal discs was found to be 483 J.cm-3 compared to that of 357 J.cm-3 for the cylindrical discs. Thus, for the hexagonal discs a significant increase (35%) in energy absorption capability is observed which is attributable to increased S/V ratio of the arrester facilitating greater heat transfer. This knowledge can be useful in designing the geometry of the device for improved functional reliability of electrical system. Key